Inhibition of long non-coding RNA ROR reverses resistance to Tamoxifen by inducing autophagy in breast cancer. Issue 6 (June 2017) - Li, Yuehua; Jiang, Baohong; Zhu, Hongbo; Qu, Xiaofei; Zhao, Liqin; Tan, Yeru; Jiang, Yiling; Liao, Mingchu; Wu, Xiaoping
This study explored the mechanism underlying long non-coding RNA ROR regulating autophagy on Tamoxifen resistance in breast cancer. Cancer tissues and adjacent normal tissues were collected from 74 breast cancer patients. Human breast cancer BT474 cells were assigned into blank, phosphate buffered saline, Tamoxifen, negative control + Tamoxifen, siROR + Tamoxifen, 3-methyladenine + Tamoxifen, and siROR + 3-methyladenine + TA groups. The expression of long non-coding RNA ROR and expressions of multi-drug resistance-associated P-glycoprotein and glutathione S-transferase-π messenger RNA were detected using quantitative real-time polymerase chain reaction. The expressions of light chain 3, Beclin 1, multi-drug resistance-associated P-glycoprotein, and glutathione S-transferase-π protein were determined using western blotting. Cell proliferation, invasion, and migration abilities were measured using 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay, Transwell assay, and scratch test, respectively. The long non-coding RNA ROR expression was higher in the breast cancer tissues than that in the adjacent normal tissues. Compared with the blank group, light chain 3 and Beclin 1 expressions were increased in the siROR + Tamoxifen group but decreased in the 3-methyladenine + Tamoxifen group; these data indicated that downregulated long non-coding RNA ROR promoted autophagy. In comparison with the blank group, multi-drug resistance-associated P-glycoprotein and glutathione S-transferase-π messenger RNA and protein expressions were reduced in the siROR + Tamoxifen group but elevated in the 3-methyladenine + Tamoxifen group, suggesting that downregulated long non-coding RNA ROR suppressed the drug resistance to Tamoxifen and the inhibition of autophagy reversed the effect of long non-coding RNA ROR on drug resistance. Compared with the Tamoxifen, negative control, and siROR + 3-methyladenine + Tamoxifen groups, the cell proliferation, invasion, and migration in the siROR + Tamoxifen group were much decreased; these results implied that downregulated long non-coding RNA ROR suppressed BT474 cell proliferation, invasion, and migration and reversed the effect of Tamoxifen on the BT474 cells. These results indicate that inhibition of long non-coding RNA ROR reverses resistance to Tamoxifen by inducing autophagy in breast cancer.